Confining spaces, resistant subjectivities: toward a metachronous discourse of literary mapping and transformation in postcolonial women's writing - Hamam, Kinana (2013)
This thesis takes as its starting point Chandra Talpade Mohanty’s argument that it is the way in which “Third World” women’s narratives are read and understood that is crucial, together with the need to locate them contextually. My original contribution to knowledge is to develop a deconstructive, cultural analysis through the re–reading of a selection of core postcolonial women’s texts written in former colonial societies, at a time prior to the full emergence of postcolonialism as a set of theoretical concepts and before feminism had developed its major contribution to academic scholarship. These theories are examined in the first three chapters of the thesis. This re–reading is of texts which arguably prefigured in many ways some of the main debates later articulated in postcolonial feminist criticism, thus (re–)interpreting them through a contemporary, critical lens. The objective of the textual analysis, among other things, is to underline the function of literary mapping in postcolonial women’s writing and the ways in which this resonates with key issues in postcolonial feminist studies. For example, the texts subvert the figure of the “universal woman” challenged by several critics, undermine images of women’s sameness, and transform marginalising spaces such as prison and home into sites of possible resistance. Overall, the main contribution of this thesis is twofold. Firstly, the interpretation of postcolonial women’s writing as a metachronous discourse of literary mapping in order to reclaim rather than deny the difference and complexity inherent in women’s texts and identities. This lends a wider dimension to the literary representations of women and justifies my attempt to order the texts as following an inverted rite of passage. Secondly, this thesis demonstrates that postcolonial women’s writing constitutes a discourse of literary activism and a cultural archive of prismatic female narratives which demands a responsive reading of the texts. This is to form a collective, critical consciousness from which, it is hoped, present and future communities of women can learn to change their lives.